Associative memory approach to modeling stock market trading patterns - Makarenko, A.; Levkov, S.; Solia, V. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2007)
The proposed research intends to use the ideas of stochastic Theory of Social Imitation (W. Weidlich, E. Calen and D. Shapiro, T. Vaga ), and of the associative memory approach to modeling the dynamical structure of polarization relationships (S. Levkov and A. Makarenko) for modeling the stock market trading patterns. The method potentially will allow us to forecast the offer and demand dynamics of a particular security, and lead to modeling of the assets price behavior. Our approach is based on the attempt to utilize the principles of certain classes of neural networks to reveal and model the underlying structure of the real dynamical process. Also the models with internal structure of brokers are considered and results of computer experiments are discussed. Приведены результаты исследования, использующего идеи стохастической теории социальной имитации (W. Weidlich, E. Calen и D. Shapiro, T. Vaga) и ассоциативной памяти в моделировании динамической структуры отношений поляризации (С. Левков и A. Макаренко) на примере фондовой биржи. Метод потенциально позволяет предсказывать динамику спроса и предложения и моделировать динамику цен активов. Предложенный подход базируется на попытке использовать принципы некоторых классов нейронных сетей для моделирования основной структуры реального динамического процесса. Рассматриваются модели брокеров с внутренней структурой и результаты компьютерных экспериментов. Наведено результати дослідження, в якому використовуються ідеї стохастичної теорії соціальної імітації (W. Weidlich, E. Calen і D. Shapiro, T. Vaga) та асоціативної пам’яті у моделюванні динамічної структури відносин поляризації (С. Левков і О. Макаренко) на прикладі фондової біржи. Метод потенційно дозволяє передбачати динаміку попиту та пропозицій і моделювати динаміку цін активів. Запропонований підхід базується на спробі використання принципів деяких класів нейронних мереж для моделювання основної структури реального динамічного процесу. Розглянуто моделі брокерів із внутрішньою структурою та результати комп’ютерних експериментів.